Rethinking Global Supply Chain Management in a Changing Environment to Develop an Integrated Freight Transportation System in Bangladesh - Sabur, H M Abdus (International Journal of Supply Chain Management, 2023)
Global supply chain management has been a critical aspect of the international business community for decades. With the rapid growth of globalization, companies have been expanding their businesses to different parts of the world, establishing cross-border partnerships and operations, and relying on global trade for their success. In recent years, the environment in which these supply chains operate has undergone significant changes. The COVID-19 pandemic, changes in government policies, and fluctuations in global trade and investment have created a more complex and challenging landscape for companies to manage their supply chains effectively. This has resulted in a need for companies to rethink their supply chain strategies, especially in developing countries such as Bangladesh. The study employs qualitative research methodology to develop an integrated freight transportation system in Bangladesh just after the changing environment of supply chain management due to COVID-19, geopolitics, and other negative impacts that brought supply chain risks/disruptions in the global freight movement from/to Bangladesh through Bangladeshi seaports. The findings of the research brought the transportation disruptions that lead to problems like operation shutdown, lost sales, late deliveries, and reputation loss remarkably. River transport emerges as the overwhelmingly preferred mode, presenting a substantial 60% of the respondents' choices whereas rail mode is only 30% but rail offers advantages in terms of efficiency and cost-effectiveness to make it a strong candidate for transporting goods Furthermore, 41.58% of respondents expressed the view that COVID-19 has significantly disrupted various activities, including the global supply chain and shipping trade. The purpose of this research is to provide a comprehensive analysis of the current state of global supply chain management in Bangladesh and to identify ways to enhance the country's integrated freight transportation system. This research will examine the existing infrastructure, policies, and practices, and suggest mechanisms for improving the efficiency and competitiveness of the supply chain in Bangladesh.